Fish Community Responses to Submerged Aquatic Vegetation in Maumee Bay, Western Lake Erie. (21st May 2018) - Miller, Jacob W.; Kocovsky, Patrick M.; Wiegmann, Daniel; Miner, Jeffrey G.
Abstract: Submerged aquatic vegetation (SAV) in clearwater systems simultaneously provides habitat for invertebrate prey and acts as refugia for small fishes. Many fishes in Lake Erie rely on shallow, heavily vegetated bays as spawning grounds and the loss or absence of which is known to reduce recruitment in other systems. The Maumee River and Maumee Bay, which once had abundant macrophyte beds, have experienced a decline of SAV and an increase in suspended solids (turbidity) over the last century due to numerous causes. To compare fish communities in open‐water (turbid) and in SAV (clearer water) habitats in this region, which is designated by the U.S. Environmental Protection Agency as an Area of Concern, and to indicate community changes that could occur with expansion of SAV habitat, we sampled a 300‐ha sector of northern Maumee Bay that contained both habitats. Using towed neuston nets through patches of each habitat, we determined that areas of SAV contained more species and a different species complex (based on the Jaccard index and the wetland fish index), than did the open‐water habitat (averaging 8.6 versus 5 species per net trawl). The SAV habitat was dominated by centrarchids, namely Largemouth Bass Micropterus salmoides, Bluegill Lepomis macrochirus, and Black Crappie Pomoxis nigromaculatus . Open‐water habitat was dominated by Spottail Shiner Notropis hudsonius, Gizzard Shad Dorosoma cepedianum, and White Perch Morone americana, an invasive species. These results indicate that restoration efforts aimed at decreasing turbidity and increasing the distribution of SAV could cause substantive shifts in the fish community and address important metrics for assessing the beneficial use impairments in this Area of Concern.